From “Folk Religion” to the “Search for Meaning”: Teaching Folklore Outside the Discipline - Primiano, Leonard (Ethnologies)

(untitled) (Association Canadienne d’Ethnologie et de Folklore, 2001)
This article discusses the challenges of assembling and teaching a course on vernacular religion in an Institute of Religious Studies. The interface of folklore and folklife studies with religious studies in the classroom offers rich opportunities for students to learn about the lived religion of others as well as themselves.